2014
DOI: 10.1534/genetics.114.168369
|View full text |Cite
|
Sign up to set email alerts
|

State Transitions in the TORC1 Signaling Pathway and Information Processing in Saccharomyces cerevisiae

Abstract: TOR kinase complex I (TORC1) is a key regulator of cell growth and metabolism in all eukaryotes. Previous studies in yeast have shown that three GTPases-Gtr1, Gtr2, and Rho1-bind to TORC1 in nitrogen and amino acid starvation conditions to block phosphorylation of the S6 kinase Sch9 and activate protein phosphatase 2A (PP2A). This leads to downregulation of 450 Sch9-dependent protein and ribosome synthesis genes and upregulation of 100 PP2A-dependent nitrogen assimilation and amino acid synthesis genes. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(154 citation statements)
references
References 77 publications
(144 reference statements)
8
145
0
1
Order By: Relevance
“…Evidence suggests that TORC1 and Snf1p/AMPK converge in the regulation of fatty acid metabolism and other outputs independently (57). A recent work provided strong evidence that Snf1p/AMPK participates as a possible upstream regulator of the TORC1 pathway under glucose-limiting conditions (58).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that TORC1 and Snf1p/AMPK converge in the regulation of fatty acid metabolism and other outputs independently (57). A recent work provided strong evidence that Snf1p/AMPK participates as a possible upstream regulator of the TORC1 pathway under glucose-limiting conditions (58).…”
Section: Discussionmentioning
confidence: 99%
“…However, Npr2 and Npr3 have little effect on TORC1 signaling under conditions of glucose starvation or stress (Hughes Hallett (296) Sec13 (322) ÎČ-propeller 2-296 1-322 Devos et al, 2004Devos et al, et al, 2014Neklesa and Davis, 2009). Taken together, these data suggest that Npr2-and Npr3-mediated signaling through TORC1 diverts energy from protein biosynthesis towards the production of amino acids and other metabolites (Hughes Hallett et al, 2014).…”
Section: Box 2 Sea/gator Homologs In Other Organismsmentioning
confidence: 99%
“…As proposed previously (28), it seems likely that some additional growth-related targets of Reg2-Glc7 could actually be phosphorylation substrates of Snf1 itself. In this regard, it has been recently reported that Snf1 phosphorylates and negatively regulates adenylate cyclase (58) and that it also inhibits the progrowth TORC1 pathway in response to glucose starvation (59,60), raising the possibility that Reg2-Glc7 might target components of the Ras-cAMP-PKA and/or TORC1 pathway. It certainly also remains possible that some relevant targets of Reg2-Glc7 could lie outside the Snf1 pathway.…”
Section: Discussionmentioning
confidence: 99%